A preparation method and application of an asymmetric gradient porous metal alloy material
By pretreating stainless steel powder and reasonably designing the gradient layer thickness, the problem of difficulty in synchronous sintering of gradient layers during sintering is solved, and the efficient preparation of asymmetric gradient porous metal alloy materials is achieved, with high filtration accuracy and high permeability.
Patent Information
- Application Number
- CN202410737562.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-06-07
AI Technical Summary
During the sintering process, the gradient layer is difficult to sinter simultaneously due to the difference in powder particle size during the sintering process, and it is prone to deformation and cracking.
By pretreating stainless steel powder, including ball milling and subvacuum low-temperature activation treatment, the powders of different particle sizes can be synchronously shrink during the sintering process, and the gradient layer thickness is reasonably designed to reduce sintering stress. The layered stacking molding method is adopted to form a single sintering molding method .
It realizes the efficient preparation of asymmetric gradient porous metal alloy materials, has high filtration accuracy and high permeability, and avoids deformation and cracking between gradient layers.
Smart Images

Figure CN118682131B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of porous metal materials, and in particular to a preparation method and application of an asymmetric gradient porous metal alloy material. Background Art
[0002] Porous metal materials are composed of a metal skeleton and internal pores, which makes porous metal materials inherit the characteristics of metal electrical conductivity and thermal conductivity, thermal shock resistance, weldability, and easy processing and molding; and because of the existence of a large number of internal pore structures, they have a series of functional characteristics, such as excellent permeability, large specific surface area and high specific strength. As a structural and functional composite material, porous metal materials solve the performance limits of porous polymer materials under harsh conditions, the tendency of "clogging" due to biological contamination, and the inherent brittleness and processing difficulties of porous ceramic materials. They have become the preferred filtration and separation materials in industrial environments such as high temperature, high pressure, and high concentration. However, with the rapid development of aerospace, nuclear industry, petrochemical industry, metallurgy and other fields, the requirements for the filtration and separation performance of porous metal materials are getting higher and higher.
[0003] Due to its own structural characteristics, that is, the pore size and pores show a gradient change along the thickness direction, gradient porous metal materials can have the performance characteristics of high permeability and high filtration accuracy at the same time, and have broad market prospects. Gradient porous metal materials include stainless steel, bronze, silver, nickel, monel, Hastelloy, Inconel alloy, etc. Among them, gradient porous stainless steel materials are the most widely demanded type of gradient porous metal materials due to their excellent corrosion resistance, temperature resistance and economy. At present, there are many preparation methods for gradient porous stainless steel materials (such as deposition method, sol-gel method, wet spraying, laser sintering, layered stacking die sintering, etc.), among which layered stacking die sintering technology is widely used in industrial production because it can prepare gradient porous materials with complex shapes, small sizes and high precision.
[0004] The change in pore size of gradient porous stainless steel materials often depends on the change in the particle size of the gradient layer powder, and the particle size of the metal powder directly affects its sintering activity. The smaller the powder particle size, the greater the sintering activity, which means that the suitable sintering temperature of the metal powder depends on the particle size. Therefore, the preparation of gradient porous materials using layered stacking die pressing sintering technology still has the following problems: (1) If the metal powder particle sizes used in each gradient layer are different, the difference in particle size makes it difficult to fully sinter the gradient layers at the same time; (2) During the sintering process, the gradient layers with different powder particle sizes cannot shrink synchronously and suffer serious deformation or even cracking. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing an asymmetric gradient porous metal alloy material and its application. The present invention pre-treats the stainless steel powder so that powders of different particle sizes can shrink synchronously during the sintering process, and reasonably designs the gradient layer thickness to reduce the sintering stress between gradient layers. The asymmetric gradient porous metal alloy material with high filtration accuracy and high permeability is prepared by a layered stacking molding and one-time sintering molding method, which can be used as a porous metal filter material.
[0006] The specific technical scheme of the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing an asymmetric gradient porous metal alloy material, comprising:
[0008] 1) The stainless steel coarse powder is ball-milled and subjected to sub-vacuum low-temperature activation treatment to make its surface slightly oxidized and have concave-convex points; the stainless steel coarse powder is mixed with copper-based metal powder and a binder to obtain a coarse powder.
[0009] In step 1), the present invention ball-mills the stainless steel coarse powder, so that the powder surface undergoes slight plastic deformation and microstructural changes, increases surface active sites, and improves the coarse powder sintering activity; then the ball-milled stainless steel coarse powder is further subjected to sub-vacuum low-temperature activation treatment, so that the powder is slightly oxidized, presents a concave-convex small point morphology, and has a higher surface energy, further improving the coarse powder sintering activity; finally, an appropriate amount of copper-based metal powder is doped in the coarse powder, and during the sintering process, when the sintering temperature is higher than the melting point of the copper-based metal, the copper-based metal powder forms a liquid phase, and due to the good wettability of the copper-based metal, it can be evenly distributed on the coarse powder matrix, further improving its sintering activity and reducing the sintering temperature. Finally, the coarse powder layer and the fine powder layer can be fully sintered at the same sintering temperature at the same time, realizing the layered stacking and molding of the asymmetric gradient porous stainless steel material and sintering molding.
[0010] 2) Mix the stainless steel fine powder and the binder to obtain fine powder.
[0011] 3) Test the bulk density of the coarse powder and the fine powder. According to the bulk density and the thickness ratio of the coarse powder layer to the fine powder layer of 2:1-5:1, weigh the required coarse powder and fine powder respectively, put them into the mold and press them into blanks.
[0012] In step 3), during the sintering shrinkage process, due to the different shrinkage rates, there is a pair of interaction forces between the gradient layers. This pair of forces restricts the shrinkage between the gradient layers. When this pair of forces is too large, it will cause deformation and cracking between the gradient layers. The smaller the particle size, the larger the specific surface area, and the higher the surface energy. Under the same sintering conditions, the sintering driving force is larger, and the radial shrinkage rate of the gradient layer is larger at the same thickness. However, the thickness of the gradient layer will also affect the sintering shrinkage rate of the powder, that is, the thicker the gradient layer, the smaller the radial shrinkage rate of the gradient layer of powder with the same particle size. The present invention effectively reduces the interaction force between the gradient layers by optimizing the thickness ratio between the gradient layers (the thickness ratio of the coarse powder layer and the fine powder layer is 2:1-5:1), which not only achieves that deformation, cracking and the like will not occur during the sintering process, but also achieves a reasonable match between the permeability and filtration accuracy of the gradient porous metal alloy material.
[0013] 4) Sintering to obtain an asymmetric gradient porous metal alloy material.
[0014] Two stainless steel powders with different particle sizes are used. After layered stacking, pressing and sintering, the powder with larger particle size forms larger pores, while the powder with smaller particle size forms smaller pores, thereby forming an asymmetric gradient porous structure.
[0015] Preferably, the particle size of the stainless steel coarse powder is 60-150 μm; the particle size of the copper-based metal powder is 30-50 μm; and the particle size of the stainless steel fine powder is 1-15 μm.
[0016] Preferably, in 1), the conditions of the sub-vacuum low-temperature activation treatment are: heating temperature (0.1-0.35)T m1 , T m1 The melting point of stainless steel, heating rate 1-5℃ / min, holding time 1-3h, vacuum degree 0.1-1Pa.
[0017] The purpose of sub-vacuum low-temperature activation treatment is to control the oxidation degree of the powder. The above parameters will determine the oxidation degree. If the powder is not oxidized enough, there will be fewer surface active points, which is not conducive to reducing the subsequent sintering temperature. Excessive oxidation will lead to poor powder pressing formability and affect the strength of the filter material after sintering.
[0018] Preferably, in 1), the copper-based metal powder is pure copper or copper-tin alloy.
[0019] Preferably, in 1), the copper-based metal powder accounts for 3-10 wt % of the total mass of the copper-based metal powder and the stainless steel coarse powder.
[0020] In order to further optimize the effect, the doping amount of copper-based metal powder needs to be controlled. If the doping amount is too little, only partial wetting can be achieved after liquefaction, and the effect is not good; if the doping amount is too much, the excess copper-based metal powder will melt, forming holes at the original position, which is not conducive to the uniform distribution of the pore size of the stainless steel filter material. In addition, excessive doping will reduce the overall strength of the filter material because copper-based metal powder is a soft phase compared to stainless steel.
[0021] Preferably, in 1), the mixing conditions are: time 5-50 h, frequency 30-70 Hz.
[0022] Preferably, in 1), the ball milling conditions are: ball-to-material mass ratio 5:1-15:1, ball milling time 0.1-2.5h, rotation speed 10-100rpm, and ball milling is carried out under an inert atmosphere; the material of the ball mill and the grinding balls is agate or corundum, and the grinding ball diameter is 0.1-2.5mm.
[0023] The low-speed, short-time ball milling process is more conducive to causing slight plastic deformation and microstructural changes on the surface of the powder without causing serious deformation and breakage, thereby increasing the surface active sites and improving the sintering activity of the coarse powder.
[0024] Preferably, in 1) and 2), the binder is one of paraffin wax powder, polyethylene wax powder or polyethylene powder, and has a particle size of 1-10 μm.
[0025] Preferably, in 1) and 2), the binder accounts for 0.5-10 wt% of the mass of the coarse powder and the fine powder, respectively.
[0026] Preferably, in 3), the pressing conditions are: pressure 150-350 MPa, holding time 10-200 s.
[0027] Preferably, in 3), the bulk density is determined in accordance with standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method".
[0028] Preferably, in 4), the sintering is a segmented continuous sintering:
[0029] The first stage: heating temperature (1-1.5)T m2 , T m2 Binder melting point, heating rate 1-10℃ / min, holding time 0.5-3h;
[0030] The second stage: heating temperature (2.5-5)T m2 , heating rate 1-5℃ / min, holding time 1-5h;
[0031] The third stage: heating temperature (0.8-1)T m3 , Tm3 Melting point of copper-based metal, heating rate 1-5℃ / min, holding time 0.5-1.5h;
[0032] The fourth stage: heating temperature (0.8-0.9)T m1 , T m1 The melting point of stainless steel, heating rate 1-15℃ / min, holding time 1-3h.
[0033] During the sintering process, the sintering temperature is more important. If the sintering temperature is too low, the phenomenon of not being sintered through may easily occur, that is, no sintering neck is formed between the powder particles, and the powder particles are only in point contact, resulting in low sintering strength. On the contrary, if the sintering temperature is too high, it will easily lead to the growth of the sintering neck and the closure of some pores, resulting in a decrease in porosity, and then a decrease in filtration flux.
[0034] Preferably, in 4), the vacuum degree of sintering is 5×10 -4 -1×10 -3 Pa.
[0035] In a second aspect, the present invention provides the use of the asymmetric gradient porous metal alloy material obtained by the above preparation method in the preparation of porous metal filter materials.
[0036] Compared with the prior art, the beneficial effects of the present invention are:
[0037] (1) The present invention realizes the preparation of asymmetric gradient porous metal alloy materials from the same metal powder with large particle size differences. The method successfully solves the problems of difficulty in synchronous sintering between gradient layers, deformation, cracking, etc. in the preparation process of asymmetric gradient porous metal alloy materials. At the same time, the method can prepare filter elements with complex shapes, simple process, high production efficiency, and easy industrial production.
[0038] (2) The asymmetric gradient porous metal alloy material prepared by the present invention has both high filtration accuracy and high filtration flux, and can be used as a porous metal filtration material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The SEM morphology of the stainless steel coarse powder used in each embodiment and comparative example.
[0040] Figure 2 The SEM morphology of stainless steel fine powder used in various embodiments and comparative examples.
[0041] Figure 3 The morphology of the stainless steel coarse powder in Example 1 is compared before and after sub-vacuum activation.
[0042] Figure 4 This is the SEM morphology of the cross section of the asymmetric gradient porous stainless steel prepared in Example 1.
[0043] Figure 5 This is the SEM morphology of the cross-section of the asymmetric gradient porous stainless steel prepared in Comparative Example 1.
[0044] Figure 6 This is the particle size distribution diagram of the asymmetric gradient porous stainless steel prepared in Example 1.
[0045] Figure 7 This is the liquid flow-pressure curve of the asymmetric gradient porous stainless steel prepared in Example 1. DETAILED DESCRIPTION
[0046] The present invention will be further described below in conjunction with the embodiments.
[0047] Overall embodiment
[0048] First, a method for preparing an asymmetric gradient porous metal alloy material comprises:
[0049] 1) The stainless steel coarse powder is ball-milled and subjected to sub-vacuum low-temperature activation treatment to make its surface slightly oxidized and have concave-convex points; the stainless steel coarse powder is mixed with copper-based metal powder and a binder to obtain a coarse powder.
[0050] In some specific implementation cases, the particle size of the stainless steel coarse powder is 60-150 μm; the particle size of the copper-based metal powder is 30-50 μm.
[0051] In some specific implementation cases, the ball milling conditions are: ball-to-material mass ratio 5:1-15:1, ball milling time 0.1-2.5h, rotation speed 10-100rpm, ball milling is carried out under an inert atmosphere; the material of the ball mill and the grinding balls is agate or corundum, and the grinding ball diameter is 0.1-2.5mm.
[0052] In some specific implementation cases, the conditions of the sub-vacuum low-temperature activation treatment are: heating temperature (0.1-0.35)T m1 , T m1 The melting point of stainless steel, heating rate 1-5℃ / min, holding time 1-3h, vacuum degree 0.1-1Pa.
[0053] In some specific implementation cases, the copper-based metal powder is pure copper or a copper-tin alloy.
[0054] In some specific implementation cases, the copper-based metal powder accounts for 3-10 wt % of the total mass of the copper-based metal powder and the stainless steel coarse powder.
[0055] In some specific implementation cases, the binder is one of paraffin powder, polyethylene wax powder or polyethylene powder, with a particle size of 1-10 μm; the binder accounts for 0.5-10 wt% of the mass of the coarse powder.
[0056] In some specific implementation cases, the mixing conditions are: time 5-50h, frequency 30-70Hz.
[0057] 2) Mix the stainless steel fine powder and the binder to obtain fine powder.
[0058] In some specific implementation cases, the particle size of the stainless steel fine powder is 1-15 μm.
[0059] In some specific implementation cases, the binder is one of paraffin wax powder, polyethylene wax powder or polyethylene powder, with a particle size of 1-10 μm; the binder accounts for 0.5-10 wt % of the mass of the finely divided material.
[0060] In some specific implementation cases, the mixing conditions are: time 10-100 hours, frequency 30-70 Hz.
[0061] 3) Test the bulk density of the coarse powder and the fine powder. According to the bulk density and the thickness ratio of the coarse powder layer to the fine powder layer of 2:1-5:1, weigh the required coarse powder and fine powder respectively, put them into the mold and press them into blanks.
[0062] In some specific implementation cases, the pressing conditions are: pressure 150-350 MPa, holding time 10-200 s.
[0063] In some specific implementation cases, the bulk density is implemented in accordance with the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method".
[0064] 4) Sintering to obtain an asymmetric gradient porous metal alloy material.
[0065] In some specific implementation cases, the sintering is a segmented continuous sintering:
[0066] The first stage: heating temperature (1-1.5)T m2 , T m2 Binder melting point, heating rate 1-10℃ / min, holding time 0.5-3h;
[0067] The second stage: heating temperature (2.5-5)T m2 , heating rate 1-5℃ / min, holding time 1-5h;
[0068] The third stage: heating temperature (0.8-1)T m3 , T m3 Melting point of copper-based metal, heating rate 1-5℃ / min, holding time 0.5-1.5h;
[0069] The fourth stage: heating temperature (0.8-0.9)T m1 , Tm1 The melting point of stainless steel, heating rate 1-15℃ / min, holding time 1-3h.
[0070] In some specific implementation cases, the vacuum degree of the sintering is 5×10 -4 -1×10 -3 Pa.
[0071] Secondly, the asymmetric gradient porous metal alloy material obtained by the above preparation method is used in the preparation of porous metal filter materials.
[0072] Specific Examples and Comparative Examples
[0073] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions summarized in the embodiments of the present invention. Obviously, the described embodiments are only used to further illustrate the present invention, but do not constitute any limitation to the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative ideas belong to the scope of protection of the present invention.
[0074] Example 1
[0075] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0076] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0077] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0078] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0079] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0080] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0081] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0082] Comparative Example 1: Compared with Example 1, the stainless steel coarse powder was not subjected to ball milling, sub-vacuum low-temperature activation and copper-based metal powder doping treatment, and other processes were the same, specifically including:
[0083] Step 1, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into 316L stainless steel coarse powder with a particle size of 60-150 μm and 316L stainless steel fine powder with a particle size of 1-15 μm, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0084] Step 2, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", test the bulk density of the mixed powder treated in step 1 and set aside;
[0085] Step 3, according to the bulk density tested in step 2 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0086] Step 4: Place the blank prepared in step 3 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0087] Comparative Example 2: Compared with Example 1, the stainless steel coarse powder was only subjected to ball milling treatment, and was not subjected to sub-vacuum low-temperature activation and doping with copper-based metal powder. Other processes were the same, specifically including:
[0088] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0089] Step 2, adding 5 wt% of polyethylene wax powder with a particle size of 1-5 μm to the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 1, respectively, and placing them in a V-type mixer at a frequency of 50 Hz for 48 hours for standby use;
[0090] Step 3, test the bulk density of the mixed powder treated in step 2 according to standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method" and set aside;
[0091] Step 4, according to the bulk density tested in step 3 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0092] Step 5: Place the blank prepared in step 4 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2(T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0093] Embodiment 2: Compared with Embodiment 1, the ball milling process in step 1 is different, and the other process flows remain unchanged, specifically comprising: step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon, and ball milling at a speed of 80 rpm for 1.25 h; step 2, placing the 316L stainless steel coarse powder treated in step 1 in a sintering furnace, evacuating the furnace to 0.15 Pa, and heating to 0.25 T at 2 ° C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0094] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0095] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0096] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0097] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0098] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0099] Comparative Example 3: Compared with Example 2, the ball milling process in step 1 is different, specifically including:
[0100] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:10 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 300 rpm for 5 hours;
[0101] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0102] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0103] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0104] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0105] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0106] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0107] Example 3: Compared with Example 1, the sub-vacuum activation treatment conditions in step 2 are different, and the other process flows remain unchanged, specifically including:
[0108] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0109] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.2 Pa, and heat to 0.2 T at 1 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 3 hours for sub-vacuum low-temperature activation treatment. After the end of the warming process, the mixture is cooled to room temperature with the furnace and taken out for use;
[0110] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0111] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0112] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0113] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0114] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0115] Comparative Example 4: Compared with Example 3, the sub-vacuum low-temperature activation treatment process is different, specifically including:
[0116] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0117] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.01 Pa, and heat to 0.5 T at 10 ° C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept at a temperature of 1 h for sub-vacuum low-temperature activation treatment. After the heat preservation is completed, the mixture is cooled to room temperature with the furnace and taken out for use;
[0118] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0119] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0120] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0121] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0122] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0123] Embodiment 4: Compared with Embodiment 1, the proportion of copper metal powder doped in step 3 is different, and the other process flows remain unchanged, specifically including:
[0124] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0125] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0126] Step 3, adding 10 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0127] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0128] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0129] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0130] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0131] Comparative Example 5: Compared with Example 4, the content of copper metal powder in step 3 is 1wt%, and the other process flow remains unchanged, specifically including:
[0132] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0133] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0134] Step 3, adding 1 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0135] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0136] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0137] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0138] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0139] Embodiment 5: Compared with Embodiment 1, the ratio of the doped binder in step 4 is different, and the other process flows remain unchanged, specifically including:
[0140] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0141] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0142] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0143] Step 4, respectively doping 7.5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0144] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0145] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0146] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0147] Comparative Example 6: Compared with Example 5, the content of polyethylene wax powder is 0.1wt%, and other process flows remain unchanged, specifically including:
[0148] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0149] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0150] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0151] Step 4, respectively doping 0.1wt% of polyethylene wax powder with a particle size of 1-5μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50Hz for 48h for standby use;
[0152] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0153] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0154] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours. After sintering, the mixture is cooled to room temperature and taken out.
[0155] Example 6: Compared with Example 1, the thickness ratio of the coarse powder layer and the fine powder layer and the pressing conditions designed in step 6 are different, and the other process flows remain unchanged, specifically including:
[0156] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0157] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0158] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0159] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0160] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0161] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 2.5:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 350 MPa, and the holding time is 30 s;
[0162] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0163] Comparative Example 7: Compared with Example 6, the thickness ratio of the coarse powder layer to the fine powder layer is 1:1, the pressing conditions are: the pressure is 500 MPa, the holding time is 60 s, and the other process flows remain unchanged, specifically including:
[0164] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0165] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0166] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0167] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0168] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0169] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 1:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 500 MPa, and the holding time is 60 s;
[0170] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 1℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 2h; then increase the temperature to 3T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up to 0.95T at 5℃ / min m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.85T at 8°C / min. m1 (T m1The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0171] Example 7: Compared with Example 1, the sintering process of step 7 is different, and the other process flows remain unchanged, specifically comprising: step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and putting them into an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0172] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0173] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0174] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0175] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0176] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0177] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.5T at 5℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 1.5h; then increase the temperature to 5T at 5°C / min m2 (T m2is the melting point of the binder), keep warm for 1h; continue to heat up at 5℃ / min to 1T m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1h; finally, the temperature is raised to 0.88T at 10°C / min. m1 (T m1 The sintering temperature is 1400°C (the melting point of 316L stainless steel), and the sintering temperature is kept for 2.5 hours. After the sintering is completed, the sintering temperature is cooled to room temperature and the sintering temperature is removed, thereby completing the preparation of the asymmetric gradient porous stainless steel filter material.
[0178] Comparative Example 8: Compared with Example 7, the sintering process is different, and other process flows remain unchanged, specifically including:
[0179] Step 1, weighing 316L stainless steel coarse powder with a particle size of 60-150 μm and agate grinding balls with a diameter of 0.5-1.5 mm in a mass ratio of 1:7.5 and placing them in an agate ball milling jar, then evacuating the jar and injecting argon gas, and ball milling at a speed of 50 rpm for 1.5 hours;
[0180] Step 2: Place the 316L stainless steel coarse powder processed in step 1 in a sintering furnace, evacuate the furnace to 0.15 Pa, and heat to 0.25 T at 2 °C / min. m1 (T m1 The melting point of 316L stainless steel is 1400°C), and the mixture is kept warm for 2 hours for sub-vacuum low-temperature activation treatment. After the end of the heat preservation, the mixture is cooled to room temperature with the furnace and taken out for use;
[0181] Step 3, adding 5 wt% of copper metal powder with a particle size of 38-45 μm to the 316L stainless steel coarse powder treated in step 2 and placing the mixture in a V-type mixer and mixing it at a frequency of 50 Hz for 24 hours for later use;
[0182] Step 4, respectively doping 5 wt% of polyethylene wax powder with a particle size of 1-5 μm into the 316L stainless steel coarse powder and the 316L stainless steel fine powder with a particle size of 1-15 μm treated in step 3, placing them in a V-type mixer and mixing them at a frequency of 50 Hz for 48 hours for standby use;
[0183] Step 5, according to the standard GB / T1479.3-2017 "Determination of bulk density of metal powders Part 3: Vibrating funnel method", the bulk density of the mixed powder treated in step 4 is tested and set aside;
[0184] Step 6, according to the bulk density tested in step 5 and the designed thickness of the coarse powder layer and the fine powder layer, the thickness ratio of the coarse powder layer to the fine powder layer is 4:1, weigh appropriate amounts of coarse powder and fine powder, load them into the mold in turn, flatten them and press them to form a blank, the pressing pressure is 250 MPa, and the holding time is 60 s;
[0185] Step 7: Place the blank prepared in step 6 in a sintering furnace for vacuum sintering. The furnace is evacuated to 1×10 -3 Pa, heated to 1.1T at 15℃ / min m2 (T m2 is the melting point of the binder, 150°C), keep warm for 3.5h; then increase the temperature to 1T at 2.5°C / min m2 (T m2 is the melting point of the binder), keep warm for 2h; continue to heat up at 5℃ / min to 0.75T m3 (T m3 The melting point of copper-based metal powder (pure copper) is 1089°C), and the temperature is kept for 1 hour; finally, the temperature is raised to 0.7T at 5°C / min. m1 (T m1 The sintering step is performed by heating the sintered steel for 3 hours, cooling the sintered steel to room temperature, and then taking the sintered steel out to complete the preparation of the asymmetric gradient porous stainless steel filter material.
[0186] Performance Testing
[0187] Performance indicators of the above embodiments and comparative examples were tested: the average pore size and porosity of the asymmetric gradient porous stainless steel filter material were tested using the BSD-PB bubble pressure membrane pore size analyzer, with reference to the standard GB / T38516-2020 "Determination of the average pore size of flow in permeable sintered metal materials"; the pure water permeability was tested in accordance with the GB / T5250-2014 "Determination of fluid permeability of permeable sintered metal materials" standard.
[0188] The test results of the average pore size, porosity and pure water permeability of the asymmetric gradient porous stainless steel filter materials prepared in the above examples and comparative examples are shown in Table 1:
[0189] Table 1 Performance data of porous stainless steel filter materials prepared in Examples and Comparative Examples
[0190]
[0191] It can be seen from Table 1 that the asymmetric gradient porous stainless steel material prepared in each embodiment has no deformation and cracking phenomenon, and is a filter material with high filtration accuracy and high filtration flux. However, in each comparative example, since the asymmetric gradient porous stainless steel material was not prepared completely according to the method of the present invention, the performance parameters or gradient layer structure were not ideal.
[0192] Figure 1 The SEM morphology of the stainless steel coarse powder used in each embodiment and each comparative example; Figure 2 The SEM morphology of stainless steel fine powder used in various embodiments and comparative examples.
[0193] Figure 3This is a comparison of the morphologies of the stainless steel coarse powder in Example 1 before and after sub-vacuum activation. It can be found from the figure that the surface roughness of the powder is significantly increased after activation, and the number of surface active sites is significantly increased.
[0194] Figure 4 This is the SEM morphology of the cross section of the asymmetric gradient porous stainless steel prepared in Example 1. Figure 4 It can be seen that the pore sizes of the coarse powder layer and the fine powder layer change, forming a gradient porous structure. Figure 5 This is the SEM morphology of the cross section of the asymmetric gradient porous stainless steel prepared in Comparative Example 1. Figure 5 Cracks can be found between the gradient layers.
[0195] Figure 6 This is the pore size distribution diagram of the asymmetric gradient porous stainless steel prepared in Example 1. Figure 6 It can be seen that the pore size of the fine powder layer is mainly concentrated in the range. The smaller the pore size, the higher the filtration accuracy. Because the fine powder layer controls the filtration accuracy, the pore size of the fine powder layer is mainly tested.
[0196] Figure 7 The liquid flow-pressure curve of the asymmetric gradient porous stainless steel prepared in Example 1 can reflect the filtration flux of the entire filter material.
[0197] The above is only a preferred embodiment of the present invention, and is not any formal or substantial limitation of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an asymmetric gradient porous metal alloy material, characterized in that include: 1) Ball-milling stainless steel coarse powder with a particle size of 60-150 μm, and performing sub-vacuum low-temperature activation treatment to make its surface slightly oxidized and have concave and convex points; mixing it with copper-based metal powder with a particle size of 30-50 μm and a binder to obtain a coarse powder; The heating temperature of sub-vacuum low temperature activation treatment is (0.1-0.35)T m1 , T m1 The melting point of stainless steel, the vacuum degree is 0.1-1Pa; 2) Mix stainless steel fine powder with a particle size of 1-15 μm with a binder to obtain fine powder; 3) Test the bulk density of the coarse powder and fine powder. According to the bulk density and the thickness ratio of the coarse powder layer to the fine powder layer of 2:1-5:1, weigh the required coarse powder and fine powder respectively, put them into the mold to form a coarse layer and a fine powder layer, and press them into blanks; 4) Sintering to obtain an asymmetric gradient porous metal alloy material.
2. The preparation method according to claim 1, characterized in that: 1), the ball milling conditions are: The ball-to-material mass ratio is 5:1-15:1, the ball milling time is 0.1-2.5h, the rotation speed is 10-100rpm, and the ball milling is carried out under an inert atmosphere; The ball mill and grinding balls are made of agate or corundum, and the diameter of the grinding balls is 0.1-2.5mm.
3. The preparation method according to claim 1, characterized in that: 1), the heating rate of the sub-vacuum low-temperature activation treatment is 1-5°C / min, and the holding time is 1-3h.
4. The preparation method according to claim 1, characterized in that: 1), the copper-based metal powder is pure copper or copper-tin alloy.
5. The preparation method according to claim 4, characterized in that: 1), the copper-based metal powder accounts for 3-10wt% of the total mass of the copper-based metal powder and the stainless steel coarse powder.
6. The preparation method according to claim 1, characterized in that: 1) and 2), The binder is one of paraffin wax powder, polyethylene wax powder or polyethylene powder, and the particle size is 1-10 μm; The binder accounts for 0.5-10wt% of the mass of the coarse powder and the fine powder respectively.
7. The preparation method according to claim 1, characterized in that: 3), the pressing conditions are: pressure 150-350 MPa, holding time 10-200 s.
8. The preparation method according to claim 1, characterized in that: 4), the sintering is a segmented continuous sintering: The first stage: heating temperature (1-1.5)T m2 , T m2 Binder melting point, heating rate 1-10℃ / min, holding time 0.5-3h; The second stage: heating temperature (2.5-5)T m2 , heating rate 1-5℃ / min, holding time 1-5h; The third stage: heating temperature (0.8-1)T m3 , T m3 Melting point of copper-based metal, heating rate 1-5℃ / min, holding time 0.5-1.5h; The fourth stage: heating temperature (0.8-0.9)T m1 , T m1 Stainless steel melting point, heating rate 1-15℃ / min, holding time 1-3h.
9. The preparation method according to claim 1 or 8, characterized in that: 4), the vacuum degree of the sintering is 5×10 -4 -1×10 -3 Pa.
10. Use of the asymmetric gradient porous metal alloy material obtained by the preparation method according to any one of claims 1 to 9 in the preparation of porous metal filter materials.
Citation Information
Patent Citations
Method for preparing asymmetric stainless steel filter disc
CN102580404A
Preparation method of continuous gradient layered porous metal printing head
CN115488340A